Body mass index and treatment outcomes following neoadjuvant therapy in women aged 45 y or younger: Evidence from a historic cohort. Issue 5 (3rd May 2016) - D'Aiuto, Massimiliano; Chirico, Andrea; De Riggi, Michele Antonio; Frasci, Giuseppe; De Laurentiis, Michelino; Di Bonito, Maurizio; Vici, Patrizia; Pizzuti, Laura; Sergi, Domenico; Maugeri-Saccà, Marcello; Barba, Maddalena; Giordano, Antonio
ABSTRACT: Purpose: Large and consistent evidence supports the role of body mass index (BMI) as a prognostic and predictive indicator in breast cancer. However, there is paucity of data specifically referred to women diagnosed at a young age across the different disease settings. We investigated the impact of BMI on treatment outcomes in 86 breast cancer patients aged 45 y or less treated with neoadjuvant chemotherapy (CT) followed by surgery. Methods: Pathologic complete response (pCR) was defined as the eradication of cancer from both breast and lymph nodes. Overall survival (OS) and disease-free survival (DFS) were calculated using the Kaplan-Meier product-limit method. Curves were compared by long rank test for significance. Potential predictors of survival were tested in Cox models. Results: We observed a pCR in 19 patients (22%). Lower values of BMI were more commonly associated with pCR (p = 0.05). Results from univariate, but not multivariate, models were somewhat supportive of higher pCR rates in leaner women (p = 0.06). None of the variables impacted DFS. OS was longer in leaner patients (medians and 95%CI: 74.6 months, 66.2–82.9 and 58.5 months, 49.6–67.4, p = 0.009). Longer OS was also related to lower T-stage, adjuvant radiotherapy (RT), and non triple negative (TN) subtype (p = 0.046, p = 0.024, and p = 0.015, respectively). Cox models confirmed the protective role of lower BMI (Hazard Ratios: 0.30, 95%CI: 0.12–0.71, p = 0.007), non TN subtype and adjuvant RT (p = 0.008 and p = 0.024). Conclusions: In young breast cancer patients treated with neoadjuvant CT followed by surgery, lower values of BMI are associated with longer OS. Our data also showed longer OS in association with a non TN molecular subtype and adjuvant RT. The modifiable nature of BMI and aggressive biologic behavior of the disease diagnosed at a young age encourage further studies to corroborate our findings.